Counterfactual Structure and Regret Intensity: Cross Linguistic Experiments on How Grammatical Mood Shapes Post Decision Emotions - Muhammad Ridwan; Belay Sitotaw Goshu (Britain International for Academic Research (BIAR-Publisher), 2025)
Regret is a counterfactual emotion requiring mental simulation of alternatives to reality. Languages differ dramatically in grammatical mood marking for counterfactuals from obligatory subjunctive (Spanish, Turkish) to optional periphrastic (English) to absent (Mandarin). Whether these grammatical differences shape regret intensity remains unknown. This review synthesizes cross‑linguistic experimental evidence testing whether obligatory counterfactual mood increases post‑decision regret, whether fine‑grained mood distinctions produce graded effects, and what mechanisms explain these effects. We integrate behavioural, eye‑tracking, and self‑paced reading experiments comparing speakers of Spanish, Turkish, German, English, and Mandarin. Standardised decision scenarios with negative outcomes were used, measuring regret intensity, counterfactual generation latency/frequency, and rumination. Multilevel mediation and within‑language mood manipulations were employed. Obligatory mood produces significantly higher regret (Cohen’s *d* up to 1.13) than optional or absent marking, mediated by faster counterfactual generation. Fine‑grained distinctions (past perfect vs. imperfect subjunctive) amplify regret selectively for irreversible outcomes. Mandarin speakers show lower regret but higher rumination, suggesting deliberative processing. Processing fluency reduced cognitive effort for counterfactual simulation when mood is obligatory is the primary mechanism. Grammatical mood is a cognitive determinant of regret intensity, not merely an expressive device. Regret’s phenomenology is partially grammatically constructed. Future research should use neurolinguistic methods, developmental designs, artificial language learning, and clinical trials of “grammatical distancing” for regret‑based disorders. Applications in legal, medical, and marketing contexts should account for cross‑linguistic mood variation.